Moralność upolityczniona jako „usprawiedliwienie” różnych form przemocy. Etycy w obronie wartości zagrożonych - Dudek, Joanna (In Gremium. Studies in History, Culture and Politics, 2021)
The text deals with the place of ethics in social life and refers to the relationship between morality and politics. It is analyzed how all attempts to dominate the moral sphere by politics lead to the denial of the essence of morality, which is based on the agency of the subject, freedom of choices and responsibility for them, the intersubjective objectivity of judgments and norms, and the pursuit of universalization of values. Reducing morality to the role of a tool in exercising political power, manipulating people, various types of politicization of this sphere by justifying the use of various forms of violence, generating social divisions, glorifying the directive of obedience, and stigmatizing selected conflicts indicate symptoms of the devastation of the moral sphere. One of the fundamental moral criteria is the justification of the truthfulness and correctness of judgments and norms, while politicized morality does not have such capacity and tries to replace it by justifying and explaining the causes of breaking moral principles. Only the proper shaping of the moral awareness of members of each community can be a barrier to the imposition and determination of ethical ideas by the authorities.